The transcultural comics of Takoua Ben Mohamed: memory and translation a fumetti. Issue 2 (May 2020) - Spadaro, Barbara
Abstract : Comics are an increasingly popular medium in the twenty-first century. Combining words and images, comics enable the expression of individual and collective histories that straddle languages and cultures, reflecting the multimodality of the cognitive and narrative processes in a multilingual, globalising world. This article proposes an original framework to understand the power of comics as a transcultural medium by exploring the production of Takoua Ben Mohamed, a graphic journalist and comics author born in Tunisia and raised in Rome. These comics visualise histories of migration and translation in Italy and the Mediterranean, questioning notions of homogeneity, authenticity and canonicity of Italian memory and culture. The article engages with the theoretical and methodological framework of the Transnationalizing Modern Languages (TML) research project, exploring the interconnected linguistic and cultural dimensions of memory and translation. The analysis identifies a series of processes termed mediation-translation in Ben Mohamed's comics, which illuminate the constitutive nature of memory and translation in contemporary processes of identification.